Sharing Different Reference Frames: How Stimulus Setup and Task Setup Shape Egocentric and Allocentric Simon Effects - Baess, Pamela; Weber, Tom; Bermeitinger, Christina (Frontiers in Psychology, 2018)
Different reference frames are used in daily life in order to structure the environment. The two-choice Simon task setting has been used to investigate how task-irrelevant spatial information influences human cognitive control. In recent studies, a Go/NoGo Simon task setting was used in order to divide the Simon task between a pair of participants. Yet, not only a human co-actor, but also even an attention-grabbing object can provide sufficient reference in order to reintroduce a Simon effect (SE) indicating cognitive conflict in Go/NoGo task settings. Interestingly, the SE could only occur when a reference point outside of the stimulus setup was available. The current studies exploited the dependency between different spatial reference frames (egocentric and allocentric) offered by the stimulus setup itself and the task setup (individual vs. joint Go/NoGot task setting). Two studies (Experiments 1 and 2) were carried out along with a human co-actor. Experiment 3 used an attention-grabbing object instead. The egocentric and allocentric SEs triggered by different features of the stimulus setup (global vs. local) were modulated by the task setup. When interacting with a human co-actor, an egocentric SE was found for global features of the stimulus setup (i.e., stimulus position on the screen). In contrast, an allocentric SE was yielded in the individual task setup illustrating the relevance of more local features of the stimulus setup (i.e., the manikin’s ball position). Results point toward salience shifts between different spatial reference frames depending on the nature of the task setup.